Matrix toughness transfer and fibre bridging laws in acrylic resin based CF composites. (November 2018) - Pini, T.; Briatico-Vangosa, F.; Frassine, R.; Rink, M.
Highlights: Effect of temperature on the contributions to fracture toughness of unidirectional composites. Partial development of the matrix process zone in the composite verified. Fibre bridging successfully modelled as a peeling of a bridging ligament. Cohesive laws for fibre bridging were experimentally determined. Abstract: The interlaminar fracture toughness, G Ic, of unidirectional carbon fibre composite laminates produced by infusion moulding with two different thermoplastic acrylic matrices, one plain and one rubber toughened, was studied. For the composite with the plain matrix fracture was dominated by failure at the fibre-matrix interface. With the toughened matrix, fracture occurred within the matrix-rich layer, although the matrix toughness could not be fully exploited due to the interaction of the fibres with the development of the process zone. A fibre bridging model based on experimentally derived cohesive laws was developed and it confirmed that fracture occurs within the matrix.